2001
DOI: 10.1139/g01-011
|View full text |Cite
|
Sign up to set email alerts
|

Polyploid formation in cotton is not accompanied by rapid genomic changes

Abstract: Recent work has demonstrated that allopolyploid speciation in plants may be associated with non-Mendelian genomic changes in the early generations following polyploid synthesis. To address the question of whether rapid genomic changes also occur in allopolyploid cotton (Gossypium) species, amplified fragment length polymorphism (AFLP) analysis was performed to evaluate nine sets of newly synthesized allotetraploid and allohexaploid plants, their parents, and the selfed progeny from colchicine-doubled synthetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
123
1
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(131 citation statements)
references
References 49 publications
5
123
1
2
Order By: Relevance
“…Liu et al (2001) did not find any loss in nine sets of newly synthesized allotetraploid and allohexaploid cotton plants, their parents, and the self-crossed progeny from colchicine-doubled synthetics among 22 000 genomic loci analyzed using AFLP or five retrotransposons using southern hybridization. The few clear cases of gene loss we report are striking exceptions to the otherwise high level of DNA sequence preservation in polyploid cotton.…”
Section: Discussionmentioning
confidence: 75%
“…Liu et al (2001) did not find any loss in nine sets of newly synthesized allotetraploid and allohexaploid cotton plants, their parents, and the self-crossed progeny from colchicine-doubled synthetics among 22 000 genomic loci analyzed using AFLP or five retrotransposons using southern hybridization. The few clear cases of gene loss we report are striking exceptions to the otherwise high level of DNA sequence preservation in polyploid cotton.…”
Section: Discussionmentioning
confidence: 75%
“…This process has been observed in paleopolyploid maize 20 and in newly synthesized allopolyploid wheat 21 , Brassica 22 and Tragopogon 23 . Some other allopolyploids, such as cotton 24 and Arabidopsis 25 , do not show many changes in their genomic sequences. Recent genome sequencing studies revealed a relatively stable genome organization in cultivated hexaploid wheat 6 and Brassica napus 9 .…”
Section: Comparative Genome Analysesmentioning
confidence: 99%
“…(14) Contrary to the rapid genomic changes observed in Brassica and wheat allotetraploids, synthetic cotton allotetraploids display a negligible amount of changes in genomic sequences. Using AFLP analysis of over 22,000 fragments, Liu et al (2001) found additive patterns for nearly all AFLP fragments examined. (58) Molecular phylogenetic analysis indicated that the orthologous genes in the progenitors evolve independently at relatively similar rates to the homoeologous loci that are combined in the allotetraploids.…”
mentioning
confidence: 95%
“…Using AFLP analysis of over 22,000 fragments, Liu et al (2001) found additive patterns for nearly all AFLP fragments examined. (58) Molecular phylogenetic analysis indicated that the orthologous genes in the progenitors evolve independently at relatively similar rates to the homoeologous loci that are combined in the allotetraploids. (59) Similarly, genomic changes in Spartina polyploids occur at a very low frequency.…”
mentioning
confidence: 95%
See 1 more Smart Citation